Clinical and Genetic Characteristics of Patients with Corticosterone Methyloxidase Deficiency Type 2: Novel Mutations in CYP11B2 - Hande Turan; Aydilek Dağdeviren Çakır; Yavuz Özer; Gürkan Tarçın; Bahar Özcabi; Serdar Ceylaner; Oya Ercan; Saadet Olcay Evliyaoğlu (JCRPE, 2021)

(untitled)
Corticosterone methyloxidase deficiency type 2 is an autosomal recessive disorder presenting with salt loss and failure to thrive in early childhood and is caused by inactivating mutations of the CYP11B2 gene. Herein, we describe four Turkish patients from two families who had clinical and hormonal features compatible with corticosterone methyloxidase deficiency and all had inherited novel CYP11B2 variants. All of the patients presented with vomiting, failure to thrive and severe dehydration, except one patient with only failure to thrive. Biochemical studies showed hyponatremia, hyperkalemia and acidosis. All patients had normal cortisol response to adrenocorticotropic hormone stimulation test and had elevated plasma renin activity with low aldosterone levels. Three patients from the same family were found to harbor a novel homozygous variant c.1175T>C (p.Leu392Pro) and a known homozygous variant c.788T>A (p.Ile263Asn) in the CYP11B2 gene. The fourth patient had a novel homozygous variant c.666_667delCT (p.Phe223ProfsTer35) in the CYP11B2 gene which caused a frame shift, forming a stop codon. Corticosterone methyloxidase deficiency should be considered as a differential diagnosis in patients presenting with hyponatremia, hyperkalemia and growth retardation, and it should not be forgotten that this condition is life-threatening if untreated. Genetic analyses are helpful in diagnosis of the patients and their relatives. Family screening is important for an early diagnosis and treatment. In our cases, previously unreported novel variants were identified which are likely to be associated with the disease.